ROLLING BALL IN BREATHING PLANE-TREE ALLEY PARADIGM - Rossler, Otto E. (European Scientific Journal, ESJ, 2013)
Sinaiâ€™s famous geometric explanation of equilibrium thermodynamics is extended towards non-equilibrium thermodynamics and cryodynamics. Specifically, â€œbreathing smooth Sinai treesâ€ are introduced. And so are â€œbreathing Sinai funnels.â€ The example demonstrates that deterministic chaos lies at the root of two fundamental physical disciplines: statistical thermodynamics and statistical cryodynamics. Quantum mechanics, computer simulation, energy technology and cosmology profit from the new consistency.